THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON SERVICE COMMITMENT (Survey in Dinas Kependudukan, Catatan Sipil dan Tenaga Kerja at Cirebon City) - Candradewini, Candradewini (Universitas Pendidikan Indonesia, 2010)
The purpose of this research is to know (1) the implementation of transformational leadership; (2) the service commitment; and (3) the influence of transformational leadership on service commitment. There are two research variables, transformational leadership (X) and service commitment (Y).This research use study method with explanatory research to explain causal relation among variables. Address the research objective it is conducted a descriptive and verification analysis by regression analysis as means of its analysis. The research was conducted on whole employees who worked in Dinas Kependudukan, Catatan Sipil dan Tenaga Kerja Cirebon City in which samples is all of its employee. The transformational leadership variable used an indicator whose was suggested by Bass, whereas the service commitment variable used an indicator whose was suggested by Sutopo and Suryanto. Generally, the results of research concluded that transformational leadership which was conducted existing in high category and the service commitment existed in high category too. Using the regression as means of verification analysis indicated that transformational leadership have positive effect on service commitment.